Stellarium sebagai Media Pembelajaran Fenomena Astronomi : Kajian Literatur - Dwitri Pilendia (Jurnal Ilmiah Wahana Pendidikan, 2022)
Astronomy is the study of celestial bodies. Some of the sub-materials included in the field of astronomy include the solar system, the sun, and astrology. Astronomy should be a very interesting subject to learn. However, most of the teachers in explaining the material did not use the right media. So students can only fantasize. In this research, a literature review will be conducted regarding the use of Stellarium as a learning medium for astronomy. The literature reviewed is the result of research that has been published in national and international journals, article, proceedings and book. With this research, it is hoped that readers can find out how to use Stellarium and its effectiveness in learning. The results showed that the use of a Stellarium was proven to increase students' interest in studying astronomy such as in the solar system.